Grain quality assessment of over-fire dried Philippine Kalinga Domarsin rice - Manuel, Mitzi Cyrelle B. (College of Home Economics, University of the Philippines Diliman, 2013)
The study characterized the physicochemical and sensory properties of Kalinga Domarsin rice subjected to over-fire drying practice produced at home scale level in Apatan, Pinukpuk, Kalinga Province. Over-fire drying practice was established to be a traditional method of drying rice for household consumption employed by farmers in Apatan, Pinukpuk, Kalinga Province as an alternative for sun-drying of paddy. The drying method involved drying ofpaddy panicles to moisture content of 14% in a wooden rack above the cooking hearth using either continuously produced fire (takes approximately 8 h to dry the bundled rice panicles) or intermittent heatwhile cooking household food (takes approximately 24 h to dry the bundled rice panicles) which is usually done by women. The rice in panicles are then rotated to the side to expose the other parts of the bundled rice panicles to the heat below the drying rack, and collection of bundled rice panicles after drying. It was established that approximately 40 bundled rice panicles can be dried over-fire using the over-fire dryers which differ in style depending on whether these over-fire dryers were built on a traditional or modern house structures that are present in Apatan, Pinukpuk, Kalinga Province. Traditional hand-milling of the dried paddy involved pounding the grains using mortar and pestle. Over-fire dried hand-pound Kalinga Domarsin rice grain samples were rated Grade 5 only in grain quality due to high percentage of broken grains but was found to have long grain size, good elongation property, intermediate amylose content, intermediate gelatinization temperature and hard gel consistency. Grain breakage of over-fire dried paddy was attributed to subsequent hand-pounding process. Cooked over-fire dried hand-pound Kalinga Domarsin rice was found to be not significantly different at 95% confidence level in terms of overall acceptability compared with cooked sun-dried rice sample except that redness scores were found more acceptable for over-fire dried rice. Cooked over-fire dried hand pound Kalinga Domarsin rice was described as slightly glossy with reddish brown color, moderately loose cooked grain appearance, with moderate aroma and moderately sweet taste, very distinguishable kernels, slightly hard, moderately cohesive, slightly sticky, moderately chewy, and moderately rough grain texture. Darker color of cooked over-fire dried Kalinga Domarsin test rice sample relative to sun-dried sample were attributed to inherent brown rice bran color on the rice endosperm, possible Maillard reactions and the reaction of carbonyls from wood smoke with amino groups in the rice grain. It was recommended that the over-fire drying practice be introduced in areas where paddy drying becomes difficult during the rainy season especially in mountainous and remote areas.